2017
DOI: 10.3390/molecules22050748
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Onchocerca and Anti-Caenorhabditis Activity of a Hydro-Alcoholic Extract from the Fruits of Acacia nilotica and Some Proanthocyanidin Derivatives

Abstract: Acacia nilotica fruits with high tannin content are used in the northern parts of Cameroon as anti-filarial remedies by traditional healers. In this study, the hydro-alcoholic fruit extract (crude extract (CE)) and, one of the main constituents in its most active fractions, (+)-catechin-3-O-gallate (CG), as well as four related proanthocyanidins, (−)-epicatechin-3-O-gallate (ECG), (+)-gallocatechin (GC), (−)-epigallocatechin (EGC) and (−)-epigallocatechin-3-O-gallate (EGCG), were assessed for their potential i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Other gallic acid analogues were isolated from the fruits of Acacia nilotica from the northern areas of Cameroon [54]. (+)-catechin-3-O-gallate, and four related proanthocyanidins: (+)-epicatechin-3-O-gallate, (+)-gallocatechin, (−)-epigallocatechin and (−)-epigallocatechin-3-O-gallate were all isolated and evaluated against C. elegans and O. ochengi .…”
Section: Chemical Classes Of Natural Compounds Described As Anthelminmentioning
confidence: 99%
“…Other gallic acid analogues were isolated from the fruits of Acacia nilotica from the northern areas of Cameroon [54]. (+)-catechin-3-O-gallate, and four related proanthocyanidins: (+)-epicatechin-3-O-gallate, (+)-gallocatechin, (−)-epigallocatechin and (−)-epigallocatechin-3-O-gallate were all isolated and evaluated against C. elegans and O. ochengi .…”
Section: Chemical Classes Of Natural Compounds Described As Anthelminmentioning
confidence: 99%
“…These peaks corresponded to catechin (Wulf et al, 2008) and epicatechin gallate (Salem et al, 2011), respectively. The occurrence of these compounds in V. nilotica has been reported (Khalid et al, 1989b;Dikti Vildina et al, 2017). Catechins were found to possess antiplasmodial activity by inhibiting both the ATPase and chaperone functions of the P. falciparum heat shock proteins (PfHsps) through direct binding to PfHsp70-1 and PfHsp70-z (Zininga et al, 2017).…”
Section: Dereplication Of Active Principlesmentioning
confidence: 99%
“…Several in vitro assays involving different types of mammalian cells have been used for high-throughput screening of toxicity effects of potential medicinal compounds as well as to identify potential safety (39,71). Certain chemical constituents of medicinal plants are found to have a hemolytic or anti-hemolytic effect on animal erythrocytes (44,72,73).…”
Section: Cytotoxicity Effectmentioning
confidence: 99%
“…The methanol extracts of seed and husk showed low toxicity effects to the tested human lymphocyte at 100 ug/mL. Dikti Vildina et al used Caco-2 cell lines as model to evaluate the cytotoxicity effect of fruit extracts of A. nilotica (increasing concentrations up to 100 or 150 µg/mL) prior to in vivo toxicological studies (39). The results demonstrated that the viability of the tested human intestinal Caco-2 cells is inhibited by the crude extract of A. nilotica (mean CC 50 93.2 ± 1.1 µg/mL (µM)).…”
Section: Cytotoxicity Effectmentioning
confidence: 99%